(111)In-exendin uptake in the pancreas correlates with the β-cell mass and not with the α-cell mass - Brom, Maarten; Joosten, Lieke; Frielink, Cathelijne; Boerman, Otto; Gotthardt, Martin (Diabetes (New York, N.Y.), 2015)
Targeting of the GLP-1 receptor with (111)In-labeled exendin is an attractive approach to determine the β-cell mass (BCM). Preclinical studies as well as a proof-of-concept study in type 1 diabetic patients and healthy subjects showed a direct correlation between BCM and radiotracer uptake. Despite these promising initial results, the influence of α-cells on the uptake of the radiotracer remains a matter of debate. In this study, we determined the correlation between pancreatic tracer uptake and β- and α-cell mass in a rat model for β-cell loss. The uptake of (111)In-exendin (% ID/g) showed a strong positive linear correlation with the BCM (Pearson r = 0.82). The fraction of glucagon-positive cells in the total endocrine mass was increased after alloxan treatment (26% ± 4%, 43% ± 8%, and 69% ± 21% for 0, 45, and 60 mg/kg alloxan, respectively). The uptake of (111)In-exendin showed a negative linear correlation with the α-cell fraction (Pearson r = -0.76). These data clearly indicate toward specificity of (111)In-exendin for β-cells and that the influence of the α-cells on (111)In-exendin uptake is negligible.